Inoculation methods of native strains of Trichoderma sp. and their effect on the growth and yield of quinoa - Leon Ttacca, Betsabe; Ortiz Calcina, Nora; Pauro Flores, Luis; Borja Loza, Rodrigo; Mendoza-Coari, Paul; Palao Iturregui, Luis (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
The use of endophytic fungi is an effective alternative to control pathogens, improve plant metabolism and yield in crops. The objective of this study was to assess the effect of five different strains of Trichoderma sp. on the growth and yield of quinoa plants (Chenopodium quinoa Willd) by using two methods of inoculation: a) pelleted seed, and b) drenching with the endophytic fungi. A completely randomized design with a 2 x 5 factorial arrangement, plus a control with five repetitions was used. The 11 treatments were evaluated with five repetitions. Yield, and aerial and root growth variables were determined. There were no interactions between strains and inoculation methods for aerial plant growth, but there were for root growth and yield. The seed pelleting method produced a higher aerial growth compared to the drench method. In root length, the greatest values were found with the TE-7 and TE-126 strains combined with the pelleted seed method. Likewise, the TE-126 strain induced the greatest dry biomass of roots using the same method. The yield varied between 4147.6 and 3222.7 kg.ha-1 in most of the strain-method combinations, without significant differences between them. Statistically, the control always ranked last, indicating the importance of the seed inoculation. Trichoderma sp. produced increases in vegetative growth and quinoa yield, with TE-7 and TE-126 being the best strains. Furthermore, seed pelleting promoted vegetative growth of the plants, while grain yield was not affected by the inoculation method.